The Nutrition Program Among Preschoolers of Dumaguete City: Perception on Implementation and Impact - Naranjo, Michele A.; Honculada, Jin A.; Mana-ay, Alvyn Klein A.; Riconalla, Ana Vee A. (Silliman Journal, 2022)
This paper examines the extent of the implementation of the nutrition programs of Dumaguete City among the preschool children as perceived by the barangay captains, the barangay nutrition workers, and the mothers of the beneficiaries. The results suggest that the overall implementation of the nutrition programs of the city was “very good” after one year of implementation. However, the prevalence of malnutrition was still higher than the cutoff score. Also, some barangays despite high implementation scores had high malnutrition prevalence rates. This may be because of the fact that less significant interventions garnered higher implementation scores than those which are more significant but with low implementation ratings. The findings of this study can help local nutrition committees to improve the management of their nutrition programs in order to significantly reduce malnutrition.